Pipsqueak family genes dan/danr antagonize nuclear Pros to prevent neural stem cell aging in Drosophila larval brains - An, Huanping; Yu, Yue; Ren, Xuming; Zeng, Minghua; Bai, Yu; Liu, Tao; Zheng, Huimei; Sang, Rong; Zhang, Fan; Cai, Yu; Xi, Yongmei (Frontiers in Molecular Neuroscience, 2023)
Neural stem cell aging is a fundamental question in neurogenesis. Premature nuclear Pros is considered as an indicator of early neural stem cell aging in Drosophila. The underlying mechanism of how neural stem cells prevent premature nuclear Pros remains largely unknown. Here we identified that two pipsqueak family genes, distal antenna (dan) and distal antenna-related (danr), promote the proliferation of neural stem cells (also called neuroblasts, NBs) in third instar larval brains. In the absence of Dan and Danr (dan/danr), the NBs produce fewer daughter cells with smaller lineage sizes. The larval brain NBs in dan/danr clones show premature accumulation of nuclear Prospero (Pros), which usually appears in the terminating NBs at early pupal stage. The premature nuclear Pros leads to NBs cell cycle defects and NB identities loss. Removal of Pros from dan/danr MARCM clones prevents lineage size shrinkage and rescues the loss of NB markers. We propose that the timing of nuclear Pros is after the downregulation of dan/danr in the wt terminating NBs. dan/danr and nuclear Pros are mutually exclusive in NBs. In addition, dan/danr are also required for the late temporal regulator, Grainyhead (Grh), in third instar larval brains. Our study uncovers the novel function of dan/danr in NBs cell fate maintenance. dan/danr antagonize nuclear Pros to prevent NBs aging in Drosophila larval brains.